The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1007/s00424-022-02726-3
|View full text |Cite
|
Sign up to set email alerts
|

Mineralocorticoid receptor-antagonism prevents COVID-19-dependent glycocalyx damage

Abstract: Proinflammatory cytokines target vascular endothelial cells during COVID-19 infections. In particular, the endothelial glycocalyx (eGC), a proteoglycan-rich layer on top of endothelial cells, was identified as a vulnerable, vasoprotective structure during infections. Thus, eGC damage can be seen as a hallmark in the development of endothelial dysfunction and inflammatory processes. Using sera derived from patients suffering from COVID-19, we could demonstrate that the eGC became progressively worse in relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…Inflammation-induced degradation of the eGC, a critical component in preserving endothelial function, has been implicated in the pathogenesis of COVID-19-related endothelial dysfunction 46–48 . Utilizing an anti-AGTR1 monoclonal antibody (mAb) across various concentrations (10, 50, and 100 µg/mL), we observed concentration-dependent reductions in eGC height and increases in stiffness compared to isotype controls ( Figure 6a ).…”
Section: Resultsmentioning
confidence: 99%
“…Inflammation-induced degradation of the eGC, a critical component in preserving endothelial function, has been implicated in the pathogenesis of COVID-19-related endothelial dysfunction 46–48 . Utilizing an anti-AGTR1 monoclonal antibody (mAb) across various concentrations (10, 50, and 100 µg/mL), we observed concentration-dependent reductions in eGC height and increases in stiffness compared to isotype controls ( Figure 6a ).…”
Section: Resultsmentioning
confidence: 99%
“…There have also been several successful strategies aimed at restoring the glycocalyx to accelerate COVID-19 recovery. The mineralocorticoid receptor antagonist spironolactone has been shown to improve glycocalyx thickness in mild COVID-19 cases [40]. Another study tested whether glycocalyx degradation could be restored, cultured human primary pulmonary microvascular endothelial cells in the presence of both COVID patient sera and the heparin sulfate mimetic fucoidan.…”
Section: Coronavirus Disease 2019mentioning
confidence: 99%
“…Recent studies have shown a link between COVID-19 and endothelial glycocalyx damage, as patients with COVID-19 have impaired glycocalyx barrier function [39]. The level of glycocalyx damage may be dependent on COVID-19 severity, as in vitro findings indicate that blood derived from patients with mild symptoms reduced the glycocalyx by approximately 49%, whereas sera from patients with severe symptoms reduced the height of the glycocalyx by >60% [40]. COVID-19 severity is also related to the magnitude of elevation in blood concentrations of syndecan-1, heparinase, heparin sulfate, and hyaluronan [37,40,41 ▪▪ ,42,43,44 ▪ ,45].…”
Section: Coronavirus Disease 2019mentioning
confidence: 99%
See 2 more Smart Citations